Report from the Eighth Session of the WHO FCTC Conference of the Parties - Forrest, Ryan (Journal of Health Inequalities, 2018)
Discussions at the FCTC COP8 in October 2018 focused on strengthening implementation of the treaty in countries around the world. Key decisions included the adoption of a new Global Strategy for tobacco control, which identifies priorities for work at the global and national levels until 2025. Discussions also highlighted challenges to future progress, including the tobacco industry’s continued efforts to undermine COP negotiations and severe resource constraints.